A105 ENDOSCOPIC MUCOSAL RESECTION (EMR) OF LARGE SESSILE POLYPS: DATA FROM A MULTI-CENTER HEALTH ZONE. (26th February 2020) - Meng, Z; Lee, A; Liu, E Y; Dhillon, A S; Wong, C; Sultanian, R; Zepeda-Gomez, S; van Zanten, S; Kohansal, A R
Abstract: Background: EMR is the standard of care for management of large non-invasive colonic polyps. Current guidelines recommend repeat colonoscopy within 6 months after EMR of large sessile polyps to assess the EMR site for residual adenoma. We reviewed the outcomes and compliance to these guidelines in patients at the University of Alberta Hospital (UAH) and surrounding 7 hospitals. Aims: The primary outcome was the proportion of patients who received a follow up colonoscopy within 180 days. Methods: Retrospective data was collected on consecutive patients who had a large polyp resection (size >2cm as documented per endoscopy report) from January 1 st, 2014 to January 1 st, 2016. Information was collected on patients from UAH as well as seven surrounding hospitals within the Edmonton geographic zone. Data was extracted from electronic health records. Results: Of 258 patients identified patients, 250 had complete data. Of these 250 patients, 151 (60.4 %) were male and median age was 67 (IQR 60 - 72). Eighty-two cases (32.8%) were performed at UAH, with 168 cases (67.2%) at other hospitals. Polyps were removed by gastroenterologists (n=215, 86.0%), surgeons (n=26, 10.4%), and others (n=9, 3.6%). Fifty-two patients (20.8%) had no formal follow up on electronic health records, while 198 patients (79.2%) had a repeat colonoscopy. 57 patients (29.1 %) had a repeat colonoscopy within 180 days. The median follow-up time was 224 days (IQR 172–365). Of the 82 cases performed at UAH, 74 (90.2%) had follow up. Out of the 168 cases at the other hospitals, 124 (73.8%) had follow up (p<0.01). Sixteen (21.9%) and 41 (33.3%) cases were followed up within 180days at UAH and other hospitals, respectively (p=0.09). Of the 74 cases with follow up at UAH, 12 (15.7%) had residual tissue confirmed by pathology. Of the 124 cases at other hospitals, 26 (21.0%) had follow up (p=0.41). Median polyp size was 2.5cm (IQR 2.0cm - 3.5cm) Conclusions: Only 29.1% of patients with large sessile polyp removal in the Edmonton zone had a repeat colonoscopy within 180 days. Patients with large polypectomy performed at the academic hospital were more likely to be followed up compared to non-academic hospitals. Further validation studies with larger data sets are needed. These findings highlight the need for standardized pathways to appropriately manage and survey large polyps post-EMR. Funding Agencies: None